War and arm conflict and its effect on the human rights in Islamic law and international law: A comparative study in Yemen between 1980-2011M / Mohammed Ahmed Qasem Shaddad - Mohammed Ahmed Qasem, Shaddad (2016)
This study aims to study and analyze the war and armed conflicts and their impact on human rights in Islamic and international law; The study also targeted the legality of war; pre-emptive war on terrorism; the main causes of the armed conflicts in Yemen and their impact on human rights; the ways to resolve disputes by peaceful means; and the responsibility of states and the media in fomenting wars; other objectives of the study include the unresolved issues within the concept of war and their legitimacy in Islamic and international laws. The researcher adopted an inductive approach as well as the analytical and comparative methods, through which the legal materials and the Islamic texts were analyzed, extrapolated and compared to each other; in addition, the researcher included the research methods of questionnaire and interview within the descriptive approach. The study exposed the prohibition of war in Islamic law unlike the view of the ancient scientists, as it is not considered justified safe when it is a defensive measure, the prohibition of the killing of prisoners, and concluded the illegality of preemptive wars in international laws applied to fight terrorism in Yemen; other findings of the field study in Yemen include: the fact that the main causes of wars are political reasons and the struggle for power as confirmed by 78% of the respondents’ opinions, followed by legal reasons; the economic reasons ranked third. However, the study concluded that the major effects of wars on human rights in Yemen are economic impacts as expressed by 96% of the respondents, followed by the legal implications, then the social impacts, whereas the health effects ranked last. Some of the most important recommendations of the study comprise refraining from pre-emptive wars carried out by some countries in order to maintain their national security and protect their economic interests; the none violation of the sovereignty of states including destructing their resources; the none monopoly of power, achieving democracy in Yemen, working on an equitable distribution of wealth in society and the need to rehabilitate, train and educate all employees of the civil and military institutions on the importance of human rights in peace and war; respecting the rights of prisoners and wounded; other recommendations call for the respect of the freedom of expression and criticism during the war and after it, the handling of the health and economic effects of wars and resolving conflicts peacefully.